BIMBINGAN BELAJAR DI ERA NEW NORMAL MENURUT AJARAN ISLAM - Mat Jalil; Agam Anantama (Jurnal Bimbingan Penyuluhan Islam, 2020)
The Covid 19 pandemic is a disease outbreak that affects all citizens of the world today and has an impact on various sectors of human life.One of the sectors affected by Covid 19 is the education sector.The government requires all people to minimize face-to-face teaching and learning activities to avoid the spread of the Covid 19 virus, one of which is by using online learning.This certainly raises a number of polemics, especially in the supervision of learning that is not optimal due to online learning.Islam as a religion that teaches its people to learn and study knowledge certainly has a solution to these problems which can be used as a reference in conducting tutoring in the current new normal era.